Clinical and virological characteristics of hantavirus infections in a 2014 Croatian outbreak - Tatjana Vilibic-Cavlek; Alena Furic; Ljubo Barbic; Irena Tabain; Vladimir Stevanovic; Gordana Mlinaric-Galinovic (Journal of Infection in Developing Countries)
Introduction: Croatia is endemic for hemorrhagic fever with renal syndrome (HFRS), with both Puumala (PUUV) and Dobrava virus (DOBV) documented. Several large outbreaks were recorded in 1995, 2002, and 2012. We analyzed demographic, clinical, laboratory, and virological characteristics of HFRS cases detected in three geographically close natural foci (Ogulin, Slunj, and the Plitvice Lakes surroundings) during the 2014 outbreak. Methodology: From January to December 2014, 122 patients with suspected HFRS were tested for hantavirus IgM/IgG antibodies using an indirect immunofluorescence assay (IFA). Cross-reactive samples were further tested using a western blot (WB). For hospitalized patients from Ogulin area, clinical and laboratory data were analyzed. Results: Acute infection was documented in 57 (46.7%) patients, of whom 75.4% were hospitalized. Ten (8.2%) patients were found to be IgG seropositive. Patients were 15–69 years of age and predominantly male (74.5%). The outbreak started in winter months, with most cases recorded from May to July (80.7%). The most frequently reported symptoms were fever (96.3%), chills/shivering (62.9%), and lumbar pain (48.1%). Mild clinical form was found in 66.7% patients, moderate in 18.5%, and severe in 14.8% patients (all but one infected with PUUV). One patient died. Using IFA, 48.8% patients showed monotypic antibody response, while in 51.2%, cross-reactive antibodies were found. PUUV was confirmed in 94.7% and DOBV in 5.3% HFRS cases by WB. Conclusions: Central mountainous Croatian regions are still highly endemic areas for HFRS. A higher percentage of severe PUUV infections could be at least partly associated with a patient’s immune status.